2021
DOI: 10.1055/s-0041-1724130
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous UBA5 Variant Leads to Hypomyelination with Thalamic Involvement and Axonal Neuropathy

Abstract: The enzyme ubiquitin-like modifier activating enzyme 5 (UBA5) plays an important role in activating ubiquitin-fold modifier 1 (UFM1) and its associated cascade. UFM1 is widely expressed and known to facilitate the post-translational modification of proteins. Variants in UBA5 and UFM1 are involved in neurodevelopmental disorders with early-onset epileptic encephalopathy as a frequently seen disease manifestation. Using whole exome sequencing, we detected a homozygous UBA5 variant (c.895C > T p. [Pro299Ser]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Earlier studies in fibroblasts revealed that UBA5 mutations impair the process of UFMylation, resulting in an abnormal ER structure. Experimental and clinical findings from animal models and humans further support UBA5 aberrance as a pathophysiological cause for many abnormalities during neurodevelopment (23,24). In addition to UFM1, UBA5 was also reported to conjugate SUMO2, another ubiquitin-like protein, and activate SUMO2 in the nucleus, though details of this interaction remain to be elucidated (21).…”
Section: Uba5 and Ufc1mentioning
confidence: 95%
“…Earlier studies in fibroblasts revealed that UBA5 mutations impair the process of UFMylation, resulting in an abnormal ER structure. Experimental and clinical findings from animal models and humans further support UBA5 aberrance as a pathophysiological cause for many abnormalities during neurodevelopment (23,24). In addition to UFM1, UBA5 was also reported to conjugate SUMO2, another ubiquitin-like protein, and activate SUMO2 in the nucleus, though details of this interaction remain to be elucidated (21).…”
Section: Uba5 and Ufc1mentioning
confidence: 95%
“…58 Multiple UBA5 variants are found in patients with neurodevelopment disorders, including autosomal recessive cerebellar ataxia, hypomyelination with atrophy, early-onset encephalopathy, and early myoclonic epilepsy. 40,53,54,[59][60][61] In addition, UFC1 mutation is also present in patients with severe early-onset encephalopathy with progressive microcephaly. 55 This UFC1 mutation impairs the formation of UFM1-UFC1 intermediates, which results in widespread decrease of protein UFMylation.…”
Section: The Ufm1 Conjugation System In the Development Of Central Ne...mentioning
confidence: 99%
“…The deletion of the UFM1 promoter reduces the UFM1 activity in neuroblastoma and astroglioma cell lines 58 . Multiple UBA5 variants are found in patients with neurodevelopment disorders, including autosomal recessive cerebellar ataxia, hypomyelination with atrophy, early‐onset encephalopathy, and early myoclonic epilepsy 40,53,54,59‐61 . In addition, UFC1 mutation is also present in patients with severe early‐onset encephalopathy with progressive microcephaly 55 .…”
Section: The Ufm1 Conjugation System In the Development Of Central Ne...mentioning
confidence: 99%
“…Of the 18 additional genes from Table 2 with likely pathogenic variants, a number including SZT2, SCN10A, UBA5 have been reported in wholeexome sequencing in epilepsy subjects [19,20]. Only one homozygous mutation, a stop-gain, was observed in single individual [21], in Potassium Calcium-Activated Channel Subfamily M Alpha 1 (KCNMA), a calciumsensitive potassium channel gene which has been shown to have a role in general and early-onset epilepsy-related phenotypes [22][23][24][25][26]. This individual, a female who was diagnosed with childhood epilepsy at 12 years old, has one family member with a diagnosis of epilepsy and was assessed to have first degree of consanguinity.…”
Section: Potentially Pathogenic Rare Variants Identified In 44 Epilep...mentioning
confidence: 99%